On the instabilities in a switchable stiffness system for vibration control - Ledezma-Ramírez, Diego Francisco; Ferguson, Neil; Brennan, Michael [UNESP] (International Institute of Acoustics and Vibration (IIAV), 2016)
A strategy for vibration control in which the stiffness is switched on and off between a minimum and a maximum value within each oscillation cycle is considered in this study. The strategy has been shown to help greatly in decreasing residual vibrations, thus increasing the effective damping ratio in lightly-damped systems. This work explores the effect of the delay during the stiffness switching. In this study, it is predicted theoretically how a certain value of delay could cause instabilities, and experimental results are presented.